RECONSTRUCTION OF CRIMINAL SANCTIONS ON CORRUPTION BASED ON DIGNITY JUSTICE THEORY (Case Study On Corruption Court Decision) - Suyono Suyono (Jurnal Pembaharuan Hukum, 2018)
As a universal form of crime, corruption can not be termed as a new problem in matters of law and economics for a Nation. The development of corruption in Indonesia at this time is very dangerous development and hamper prosperity in achieving levels of Indonesian society. Corruption affects civil servants and law enforcement officers. There are several factors generally understood to mobilize human intentions to commit corruption. In other words, there habit of consumptive life. Buy goods that are not so required. There is no shame in social life with all the luxuries that do not fit the job profile. Coupled with no fear of God because of the lack of religious foundations and many other factors that are trusted public can influence a person committing corruption. The idea for the reconstruction of criminal sanctions against perpetrators of corruption based on values of justice with dignity can be realized by studying the court decision corruption case. The idea of such reconstruction is motivated by, among others, the urgency of public policy according to the law of the importance of a step in the eradication of corruption more quickly and effectively in a superb tackle extraordinary crime.